THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT AND COMPETENCE ON EMPLOYEE PERFORMANCE AND EMPLOYEE MOTIVATION AS INTERVENING VARIABLES IN THE ADMINISTRATIVE AFFAIRS OF THE SUPREME COURT REPUBLIC OF INDONESIA - Edi Sugiyono; Untung Hermawan (SEAN Institute, 2022)
This research analyzes the influence of Leadership Style, Work Environment and Competence on Employee Performance and Employee Motivation as Intervening Variables at the Administrative Affairs Agency of the Supreme Court of the Republic of Indonesia. The research method uses descriptive quantitative and statistical tools using Structural Equation Modeling (SEM). The results showed that Leadership Style had a positive and insignificant effect on Employee Motivation. Work Environment and Competence have a positive and significant effect on Employee Motivation. Leadership Style and Work Environment have a negative and insignificant effect on Employee Performance. Competence has a positive and significant effect on Employee Performance. Leadership Style, Work Environment and Competence have a positive and significant impact on Employee Performance through Employee Motivation.